Dinâmica temporal da fauna edáfica em áreas de caatinga sob pastejo caprino - Silva, Adeilson de Melo (2016)
Soil quality should not be limited to the productivity of the same, but should also involve environmental quality, human and animal health in association with food quality. The soil fauna has been the subject of studies that seek to understand the effects of human actions on the environment and used as bio-indicators of the current condition that certain environment. The objective of the research was to analyze the temporal dynamics of edaphic macrofauna and mesofauna in Caatinga areas under goat grazing with different stocking rates. The experiment was conducted in a Caatinga area of 9,6 ha divided into three subarea of 3,2 ha there with different stocking rates (A1 = 10 goats, A2 = 5 goats and A3 = no goats), in the Estação Experimental de São João do Cariri- PB, belonging to the Federal University of Paraiba, Agricultural Science Center. Provid traps were used to capture the macrofauna; metal rings for soil + litter collect and extractor Berlese Tullgren for mesofauna extraction. Among the macrofauna, ants were the most abundant individuals in the three environments and the mites for mesofauna. There was no difference in orders wealth between areas. However, the higher Shannon and Pielou index were found in Area 3 and the highest Simpson index, registered in Area 1. Nighttime proposed higher diversity and Equitability while the daytime, higher dominance. Spiders, centipedes and scorpions occurred in greater proportion in the A3 environment then by A2 and A1. The dynamics of mites and springtails was more balanced in Area 3, then Area 2 and Area 1. The heterogeneity of each environment and rainfall reflected in the high variation in the data. In general, the soil fauna tends to emerge after rain events and how mouch best distributed these events, there is a predisposition to a larger in the dynamics balance of soil fauna.